Transportation Model for Optimizing Betta Fish Distribution in Kediri City, East Java - Hutami Putri Puspitasari; Budi Setiawan; Agus Tjahjono (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2020)
The purpose of this study is to analyze the transportation costs and the optimal allocation of betta fish distribution in Kediri City. The research method is quantitative descriptive with the selection of respondents using the cluster sampling method and data processing using a linear program in the transportation model. There are several obstacles in the process of distributing betta fish in the City of Kediri related to costs that make distribution not optimal, so the linear program is used to analyze the existing constraints to achieve minimization of transportation costs with LINDO (Linear Interactive Discrete Optimizer) software. The results showed that the total actual transportation cost of betta fish distribution was IDR 1.545.773 and at optimal conditions IDR 633.936. Total cost in this optimal condition is lower than the actual condition, where the difference is IDR 911.837 which shows that the cost of distributing betta fish in Kediri can be saved by 58.9 with the most optimal allocation and carrying capacity of each cultivator.